PENGEMBANGAN BAHAN AJAR DENGAN 3D PAGEFLIP PROFESSIONAL PADA MATERI PECAHAN KELAS IV SD DALAM KURIKULUM MERDEKA - Yulia Friska, Sonia; Andryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of students' low conceptual understanding of fractions, which are abstract in nature, and the lack of interactive learning media usage at SDN 104/VIII Sumber Sari. Furthermore, the implementation of the Independent Curriculum (Kurikulum Merdeka) demands the integration of technology to support student-centered learning. This study aims to develop digital-based teaching materials using the 3D Page Flip Professional application on fractions material that meets the criteria of valid, practical, and effective. The type of this research is Research and Development (R&D) using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 4th-grade students of SDN 104/VIII Sumber Sari. Data collection instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests (pre-test and post-test). The results showed that: (1) The teaching materials were declared very valid based on the assessment of material experts, media experts, and language experts with an average percentage of [87 %]; (2) The teaching materials were declared very practical to use based on teacher and student response questionnaires with a percentage of [88 %]; (3) The teaching materials were declared effective in improving student learning outcomes as indicated by the N-Gain score of [0,71] in the [High] category. Based on these results, it can be concluded that 3D Pageflip teaching materials on fractions are suitable and effective for use as learning media in 4th-grade elementary school.